Quantum Quench in the Transverse Field Ising Chain II: Stationary State Properties - Calabrese, P; Essler, F; Fagotti, M (2012)
We consider the stationary state properties of the reduced density matrix as well as spin-spin correlation functions after a sudden quantum quench of the magnetic field in the transverse field Ising chain. We demonstrate that stationary state properties are described by a generalized Gibbs ensemble. We discuss the approach to the stationary state at late times.